PROFESSIONAL ATTRIBUTES OF INTERNAL AUDITORS IN RIAU - Nanda, Satria Tri (LLDIKTI Wilayah X, 2018)
This research aims to identify the factors influencing the audit quality of auditors at Inspektorat Provinsi Riau. The population in this research were auditor, examiner, assistant examiner, and P2UPD (Pengawas Penyelenggara Urusan Pemerintah di Daerah) in charge at the Inspectorate in Riau Province and all Inspectorates in Districts and Cities in Riau Province. A total of 290 set of questionnaire were sent and a number of 184 of questionnaires were processed. Using regression analysis conducted by SPSS, the hypotheses testing analysis results show that experience, responsiveness, professional care, executive involvementt, planning and auditability have significant and positive effect on audit quality. These results indicate that the higher the levels of experience, responsiveness, professional care, executive involvement and auditability of Inspectorate officials, the better the quality of audit performed by the Inspectorate Officials of Riau Province.